Analysis of the reliability of two force platforms for the simultaneous collection of kinetics variables - Antunes, N.; Medeiros, F. B.; de Campos Abreu, E. A.; Pereira de Andrade, A. G.; Menzel, H. J. K.; Ribeiro Santos Araujo, S. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The bilateral force asymmetry between lower-body limbs is seen as one of the major causes of injury and decreased performance in sport. The diagnosis can be done through many measuring methods, instruments and protocols. One of the most validated methods in literature is the vertical jump with countermovement performed on a force platform. Many studies show measurement protocols of jumps performed on a force platform where the jumps are carried out in a unipodial or bipodial manner and the data collection takes place in an alternated or sequential way. This study intends to assess the reliability of two force platforms measuring (maximum force and impulse) simultaneously. The results have indicated that the method used is reliable for the collection of the mentioned variables.